Lembaga Manajemen Kolektif Nasional (LMKN) sebagai Penilai Nilai Ekonomi dalam Pengikatan Hak Cipta Musik dan Lagu sebagai Objek Jaminan Fidusia - Sri Handayani; Joni Emirzon; Annalisa Yahanan (Badan Strategi Kebijakan Hukum, 2023)
One of the creations protected by copyright is songs and/or music. Legal protection for them is a necessity in order to create a conducive climate to the development of music industry in Indonesia. In order to facilitate song and/or music writers with better control over their works, they can appoint representatives to regulate the management of their royalty, in this case LMKN (The National Collective Management Institute). Law number 28 of 2014 concerning copyrights regulates that copyright can be used as an object of fiduciary guarantee. However, its use is still hampered by the fact that the economic value of music and song copyrights cannot be determined easily, especially if it is used for fiduciary guarantee. Most banks do not accept it for loan collateral. The objective of this research was to analyze the roles of LMKN as the determiner of the economic values of song and music copyrights for the purpose of binding them for objects of fiduciary guarantee. This normative study uses statutory approach, conceptual approach, analytical approach, and futuristic approach. The determination of the economic values of song and music copyrights can be done by LMKN, a one- stop service institution that collects the royalty of music and song in Indonesia. The National Collective Management Institute (hereinafter briefly referred to as LMKN) as an institution that can provide an appraiser of the economic value of Music and Song Copyrights. The use of SILM (a music and song information system and data center) can help the estimation of music and song's economic value based on the royalty accepted by the art's creator or copyright holder. The amount of royalty can determine the binding of music and song copyrights for the objects of fiduciary guarantee.